2019
DOI: 10.1111/1753-6405.12872
|View full text |Cite
|
Sign up to set email alerts
|

Educating for Indigenous public health competence – how do we stack up in Australia?

Abstract: Objective: Internationally, work is underway to develop or revise public health graduate competencies, of which Indigenous public health competencies are a subset in Australia. This paper outlines the summative results from a review of Master of Public Health (MPH) programs undertaken to determine the level of coverage of Indigenous health in core content and to explore factors that influence the extent of integration. Methods: Of the 22 Australian universities offering an MPH program at the commencement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The PHERP review suggested several reasons for a low participation rate, including a lack of Indigenous content in curriculum and a lack of support for Indigenous graduates, and there has been some notable work in this area, including the development of curriculum frameworks for Aboriginal and Torres Strait Islander public health education 18 . However, a recent review of Australian public health courses suggests Indigenous health competencies are not always covered 19 . This decline may be reflective of increased barriers within public health education, or increased access to other degrees, and future research should determine which of these is the case.…”
Section: Discussionmentioning
confidence: 99%
“…The PHERP review suggested several reasons for a low participation rate, including a lack of Indigenous content in curriculum and a lack of support for Indigenous graduates, and there has been some notable work in this area, including the development of curriculum frameworks for Aboriginal and Torres Strait Islander public health education 18 . However, a recent review of Australian public health courses suggests Indigenous health competencies are not always covered 19 . This decline may be reflective of increased barriers within public health education, or increased access to other degrees, and future research should determine which of these is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Each competency within public health begins with an introduction of the underpinning knowledge around public health history and the rationale of appropriate study designs and research methods (Coombe et al ., 2019). Yet, without embedding Indigenous historical and current social conditions that continue to further sustain inequitable power dynamics and legitimise a violent health system, it is all but meaningless (Durey and Thompson, 2012).…”
Section: An Indigenist Framework In Public Health Educationmentioning
confidence: 99%
“…Public health needs to equip graduates with a criticality about it as a discipline which includes an understanding that ‘Indigenous health’ as conceived through public health has failed Indigenous peoples, thus enabling ‘less leeway for systemic or interpersonal bias in public health and clinical decision-making’ (Paradies et al ., 2008). The limited capacity of non-Indigenous academics teaching Indigenous health to engage in this disciplinary criticality impacts their ability to constructively comprehend and address challenges of systematic failures, thus subsequently affecting their willingness and ability to integrate Indigenous content (Coombe et al ., 2019). Consequently, future public health professionals will not be well-equipped to critically evaluate and reflect on how the values, norms and practices of contemporary structures and institutions consider one group superior to others (Bastos et al ., 2018).…”
Section: An Indigenist Framework In Public Health Educationmentioning
confidence: 99%
See 2 more Smart Citations